Calcareous nannoplankton fluctuation within the Albian-Cenomanian Boundary Event of the Tethyan Himalaya - Melinte-Dobrinescu, Mihaela; Chen, Xi; Anton, Eliza; Apotrosoaei, Vlad; Yao, Hanwei (Frontiers in Earth Science, 2024)
A hemipelagic succession 29m thick, situated in South Tibet within the Tethyan Himalaya tectonic unit, has been investigated for its calcareous nannofossil content. A total of 17 samples were subject to qualitative and semi-quantitative analysis. The studied interval belongs to the upper Albian-lowermost Cenomanian and extends into the UC0 nannofossil zone; based on the last occurrence of Hayesites albiensis, the UC0a and UC0b-c subzones were recognized. The most abundant nannofossil of the Youxia section is Watznaueria barnesiae. Other common taxa are Eiffellithus turriseiffelii, Eprolithus floralis, Rhagodiscus spp., and Zeugrhabdotus spp. In the lowermost part of the studied section, below the beginning of the Albian-Cenomanian Boundary Event (ACBE), i.e., prior to the δ13C positive excursion related to OAE1d, the nannofossils confined to high paleolatitudes, namely Repagulum parvidentatum, Seribiscutum primitivum, and Sollasites horticus, are present with a low abundance. This occurrence is believed to be evidence of a short episode of cooler surface waters linked to a transgressive event. The nannofossil abundance and diversity, along with the fluctuation patterns of the nutrient and temperature indices throughout the section, reflects a primary signal of mesotrophic to eutrophic conditions from the base of the succession up to the two oldest δ13C peaks of ACBE, both late Albian in age and within the OAE1d. By contrast, the dominance of Watznaueria barnesiae, representing more than 80% of the total assemblages, along with the significant drop in abundance and diversity shown by nannofossils within late phases of ACBE, are interpreted as a diagenetic signal. Mesotrophic to eutrophic conditions returned towards the top of the studied succession, where Biscutum constans and Zeugrhabdotus erectus again show a higher abundance.